MSTN knockout enhances the production of MYOD1-mediated steak-type cultivated meat - Kyeong-Hyeon Eom; Dayi Jeong; Jae-Yoon Choi; Gyeong-Min Gim; Soo-Young Yum; Sumin Jin; Hojae Bae; Goo Jang (Journal of Animal Science and Biotechnology)
Abstract Background As the global population increases, the demand for protein sources is expected to increase, driving the demand for cell-based cultivated meat. This study aimed to enhance the productivity of cultivated meat through optimization of the cell source and organization process. Results We engineered fibroblasts into myogenic cells via non-viral introduction of the MYOD1 gene, avoiding viral methods for safety. After confirming the stable derivation of myogenic cells, we combined knockout (KO) of MSTN, a negative regulator of myogenesis, with MYOD1-mediated myogenesis to improve cultivated meat production. Primary cells from MSTN KO cattle exhibited enhanced myogenic potential. Additionally, when tested in immortalized fibroblasts, myostatin treatment reduced MYOD1-induced myogenesis in two-dimensional cultures, while MSTN knockout increased it. To achieve muscle-like cell alignment, we employed digital light processing (DLP)-based three-dimensional (3D) bioprinting to organize cells into 3D groove-shaped hydrogels. These bioactive hydrogels supported stable cell proliferation and significantly improved muscle cell alignment. Upon differentiation into myotubes, the cells demonstrated an ordered alignment, particularly the MSTN KO cells, which showed highly efficient differentiation. Conclusions The integration of genetic modification and advanced DLP 3D bioprinting with groove-patterned hydrogels provides an effective strategy for producing high-quality, muscle-aligned cultivated meat.